Tackling Social Problems in Branches Muhammadiyah Gedangan - Annis Wati; Vindy Aprilia; Lailatul Adkha; Dita Ariyanti (Proceedings of The ICECRS, 2020)
The purpose of this study was to determine social problems in the Muhammadiyah branch of Gedangan and its remedies, and to find out the history of the establishment of the Muhammadiyah branch in Gedangan. This research is a descriptive qualitative research through interviews and direct observations on the head of the Muhammadiyah branch of Gedangan. Based on the results of research on social problems in the Muhammadiyah Gedangan branch along with the history of the establishment of the Muhammadiyah Gedangan branch, it was founded in 1990 until now. The social problem in the Muhammadiyah Gedangan branch is that it only has one business charity in the field of education, on the side of life the education sector stands out among minority communities, as a result there are various kinds of social problems, namely experiencing a lack of students and the impact from the economic side, and from the side the life of the minority community is very influential, because many residents do not want to enroll their children in the school. As a result of the impact of social minority problems, many people think that the school is only for Muhammadiyah people and the cost is expensive.